A Periodic Review Inventory Control of Medicine at Hospital - Devi Ajeng Efrilianda; Manasya Khulafa Alief Rahman (Journal of Advances in Information Systems and Technology, 2024)
One of the important problems in inventory control is the problem of managing stock in the system. In the case of medicine product storage management, over inventory will lead to high storage costs and increase the risk of spoilage or expiration. While the shortage of inventory causes demand that cannot be fulfill. In addition, optimal storage management in the case of medicinal products is also an effort to create a socially responsible supply chain. Lack of product management causes products to experience stockout, resulting in low service levels at the hospital. This study aims to create a storage management model using periodic reviews so that the medicines in the hospital do not experience stockout or overstock and the hospital does not experience losses due to this. The periodic review method was chosen because it is considered capable of being a model of the problems faced by hospitals in storage. The calculation of the periodic review method requires data obtained from hospitals, such as demand data, lead time data, drug data, cost data, so the data used is primary data. After obtaining the required data, a periodic review is calculated which will become a benchmark for hospitals to place orders for medicines that have run out based on the demand for medicines and the time period from the sender of these medicines and so on